Dampak Aksesibilitas Kabupaten Penajam Paser Utara Dan Kabupaten Paser Pada Kota Balikpapan - Tiara Safitri; Adi Wijaya; Emmilya Umma Aziza Gaffar (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Abstract, Impact of Accessibility in North Penajam Paser District and Paser District in Balikpapan City. Guided by Mr. H. Adi Wijaya as mentor I and Emmilya Umma Azzia Gaffar as mentor II               The aim of this study is to find out how the accessibility effects of the Northern Penajam Paser district and Paser districts in the city of Balikpapan and which regions were among the Northern Penajam Paser districts and Paser districts which had the highest level of accessibility in the city of Balikpapan.The result of the impact of accessibility that occurred in Penajam Paser Utara and Paser districts in Balikpapan city greatly influenced the development of each region, giving rise to attractiveness and thrust in accordance with the region's shortcomings, the driving factor (a) the slow distribution of existing development in sharpen and paser regions (b) Lack of transportation facilities and infrastructure (c) Lack of availability of higher education facilities in northern Pasajam Pasajam District, while the attracting factors are (a) Number of jobs in Balikpapan (b) Opportunities to obtain education better in the city of balikpapan (c) The size of the population of the city of balikpapan is considered promising to improve their welfare. The region that has the greatest accessibility in the city of balikpapan is the northern paser sharpening district